Structural and computational glycobiology: immunity and infection (2015)
Interest in understanding the biological role of carbohydrates has increased significantly over the last 20 years. The use of structural techniques to understand carbohydrate-protein recognition is still a relatively young area, but one that is of emerging importance. The high flexibility of carbohydrates significantly complicates the determination of high quality structures of their complexes with proteins. Specialized techniques are often required to understand the complexity of carbohydrate recognition by proteins. In this Research Topic, we will focus on structural and computational approaches to understanding carbohydrate recognition by proteins involved in immunity and infection. Particular areas of focus include cancer immunotherapeutics, carbohydrate-lectin interactions, glycosylation and glycosyltransferases.